Pengabdian Masyarakat dengan “Edukasi KB Pasca Persalinan pada Kelas Ibu Hamil” di Wilayah Kerja Puskesmas Buaran Kota Pekalongan - Setyowati, Ana; Maslikhah, Maslikhah; Baroroh, Ida (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Contraception is the prevention of fertilization of an egg by a sperm cell or prevention of the attachment of a fertilized egg to the uterine wall. The contraception program is one effort that can be made to control the birth rate. The use of postpartum birth control is an important aspect in reproductive health and family planning. In an effort to achieve sustainable development goals, attention to the welfare of mothers, children and families is becoming increasingly urgent. The aim of this service is to provide postpartum family planning education to pregnant women to actively participate in the success of family planning activities. The method used in this community service activity begins with post-natal family planning education, various types of post-natal family planning according to needs. The result of this activity was an increase in the knowledge of respondents, the majority of whom were in the good category (87.5%). Overall, this service activity can be said to be good because it has succeeded in increasing respondents' knowledge and understanding regarding postpartum family planning.